ANALISIS RUGI-RUGI DAYA DAN JATUH TEGANGAN PADA SALURAN TRANSMISI 150 KV GARDU INDUK PANDEAN LAMPER-PUDAK PAYUNG - Khoirunnisa, Ulfah; Bayu Murti, Budi; Budiyanto, Maun (ITP Press, 2024)
The need for electrical energy now extends to remote areas. According to KESDM, the number of household and industrial customers in Central Java and DIY increased from 2020 to 2022. To maintain system balance and accommodate the increasing load, power distribution efficiency is required. At the transmission stage, electrical energy is transferred on a large scale from the power plant to the substation through a 150 kV SUTT. During the distribution of energy, power losses and voltage drops often occur, which are influenced by transmission distance, conductor cross-sectional area, conductor resistance, and load. To ensure that power losses and voltage drops remain below 5% according to SPLN No. 72 of 1987, it is necessary to evaluate whether the transmission load of the Pandean Lamper-Pudak Payung Substation is in accordance with the capabilities of the 1xACSR 240/40 conductor. The research method uses voltage and current data at peak load which is analyzed by manual calculation and ETAP 19.0.1 simulation. The results of the percentage comparison of manual calculation and simulation of power losses and voltage drops are between 0.5%-1%. The largest power loss occurred on January 15, 2024 amounting to 543 kW from manual calculation and 563.5 kW from simulation results. The percentage value of power losses reached 5.66%, which exceeded the SPLN limit. The highest voltage drop of 2.01% occurred on the same date. Based on this value, the Pandean Lamper-Pudak Payung Substation transmission line has reached its maximum load and it is necessary to increase transmission capacity by adding conductors.